2019
DOI: 10.3390/ma12233888
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Melilotus officinalis Growth to the Composition of Different Topsoil Substitute Materials in the Reclamation of Open-Pit Mining Grassland Area in Inner Mongolia

Abstract: The purpose of this study was to reveal that reconstructed soil composed of different types and proportions of materials has different effects on the growth of Melilotus officinalis, and to determine the most suitable formula of reconstructed soil materials to use for soil replacement. Using topsoil, coal gangue, fly ash, and rock and soil stripping materials from Shengli Mining Area of Inner Mongolia as raw materials, stratified and mixed pot experiments were carried out in a greenhouse using different propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The ecological restoration of coal mining areas is strongly limited by soil nutrient deficiencies, unstable soil structures, and slow growth rates of the vegetation. Soil reconstruction is the core component of land reclamation, and thus the quality of reconstructed soil directly determines the quality of land reclamation 1 . Coal gangue and fly ash are produced during coal mining, processing, and use.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological restoration of coal mining areas is strongly limited by soil nutrient deficiencies, unstable soil structures, and slow growth rates of the vegetation. Soil reconstruction is the core component of land reclamation, and thus the quality of reconstructed soil directly determines the quality of land reclamation 1 . Coal gangue and fly ash are produced during coal mining, processing, and use.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest challenges for the ecological reconstruction of mine lands are derived from scarce fertile soil 31 , 32 . The reconstructed soil, which mainly comprises raw soil and is similar to the soil parent material used in the reclamation of coal gangue dump land, was characterized by a lack of organic matter, weak soil structure, and an elevated salt content 31 , 33 . Mixing coal gangue with soil to reconstruct degraded soil can influence soil infiltration rates and saturated hydraulic conductivity 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…The greatest challenges for the ecological reconstruction of mine lands are derived from scarce fertile soil [34][35]. The reconstructed soil, which mainly comprises raw soil and is similar to the soil parent material used in the reclamation of coal gangue dump land, was characterized by a lack of organic matter, weak soil structure, and an elevated salt content [34,[36][37]. Mixing coal gangue with soil to reconstruct degraded soil can in uence soil in ltration rates and saturated hydraulic conductivity [38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that coal gangue is a material that can be used in fertilizer production. Furthermore, as the concentration levels of trace elements are below permissible limits, coal gangue can also be used as a substitute for soil replacement because of its low transportation cost [36,[43][44]. More critically, granular coal gangue has a morphology similar to that of the gravel currently used and contains mineral elements similar to those in soil.…”
Section: Introductionmentioning
confidence: 99%